Optimization of medium formulation on production of recombinant chitinase in escherichia coli - Mohd Faris, Mohd Yunus (2010)
Chitinase is enzyme that hydrolyzing chitin to produce N-acetyl- glucosamine. Chitinase can be found in bacteria, fungi, higher plant, insect and some vertebrates. There are a lots of applications of chitinase as the demands of the enzyme is rising high in the market due to usage in pharmaceutical, biopesticides or food industry. For this study, chitinase enzyme was expressed in recombinant bacteria using Escherichia coli as a host. The effect of various medium on expression of chitinase in Escherichia coli was conducted in this research. Five medium were studied. LB, TB, SB, SOB and 2x YT were screened. LB medium gave the best result of highest chitinase enzyme activity. Each component of LB medium was study to determine the optimize amount of composition to produce the highest enzyme activity. The best range of every composition obtained from the conventional method was 3.0 g/l to 7.0 g/l for sodium chloride, 1.5 g/l to 4.5 g/l for yeast extract and 10 g/l to 14 g/l for tryptone. The optimization was done using response surface methodology (RSM) conducted by software named Design Expert. The optimal medium composition for high soluble recombinant chitinase was determined as 3.63 g/l of sodium chloride, 4.50 g/l of yeast extract and 13.11 g/l of tryptone. From the experimental, the enzyme activity after optimization was achieved 2.291 U/ml compared to predicted response of 2.409 U/ml. This result shows increment of the activity for 82% than before the optimization which is 0.411 U/ml. It shows that the optimization of the medium formulation to improve the expression and production of chitinase was successfully conducted by using RSM.